Diagnostic sensitivity of SILVAMP TB-LAM (FujiLAM) point-of-care urine assay for extra-pulmonary tuberculosis in people living with HIV. Issue 2 (6th February 2020) - Kerkhoff, Andrew D.; Sossen, Bianca; Schutz, Charlotte; Reipold, Elena Ivanova; Trollip, Andre; Moreau, Emmanuel; Schumacher, Samuel G.; Burton, Rosie; Ward, Amy; Nicol, Mark P.; Meintjes, Graeme; Denkinger, Claudia M.; et al.
Diagnosing tuberculosis (TB) in people living with HIV (PLHIV) remains challenging in part, because of its diversity of clinical manifestations, including high rates of extra-pulmonary and disseminated disease [1]. In particular, disseminated TB, involving multiple organ systems, is associated with high mortality but often presents non-specifically, which may hinder prompt diagnosis [2, 3]. Xpert MTB/RIF (Xpert; Cepheid, Sunnyvale, CA, USA), is currently recommended by the World Health Organization (WHO) as the first line assay for evaluating a subset of extra-pulmonary TB disease (EPTB) manifestations [4]. FujiLAM point-of-care rapid urine test for TB detects a large proportion of pulmonary and traditionally difficult-to-diagnose extra-pulmonary forms of TB in hospitalised patients with advanced HIV http://bit.ly/36Dl0Eo